The impact of Klinefelter syndrome on socioeconomic status: a multicenter study. Issue 7 (29th June 2022) - Franik, Sebastian; Fleischer, Kathrin; Kortmann, Barbara; Stikkelbroeck, Nike M; D'Hauwers, Kathleen; Bouvattier, Claire; Slowikowska-Hilczer, Jolanta; Grunenwald, Solange; van de Grift, Tim; Cartault, Audrey; Richter-Unruh, Annette; Reisch, Nicole; et al.
Abstract : Klinefelter syndrome (KS) is associated with an increased risk of neuropsychological morbidity, such as learning disabilities, which may have a significant impact on socioeconomic status (SES). The objective of this study was to investigate the SES in men with KS and to associate this outcome with social participation, age at diagnosis, testosterone therapy and physical and mental health status. Men with KS were recruited in 14 clinical study centers in six European countries which participated in the European dsd-LIFE study. Two hundred five men with KS were eligible for inclusion. Male normative data from the European Social Surveys (ESS) were used for comparison. Data related to education, occupation, satisfaction with income and householding were collected. Compared to the ESS reference population, fewer men with KS achieved a high level of education (13% vs 25%, P < 0.001). There was a significant difference in having a paid job (55% vs 66%, P < 0.001), and the percentage of absence by sickness or disability was higher among men with KS (10% vs 3%, P < 0.001). Furthermore, satisfaction with current household's income was lower (32% vs 42%, P < 0.01). Lower scores for subjective general health were associated with lower scores for these outcomes. Men with KS achieve on average lower levels of education, occupation and report less satisfaction with income compared to the ESS reference population. The presence of health problems and lower scores of subjective general health was related to lower levels of occupation and lower satisfaction with income in men with KS.